Business Management: Analysis of Entrepreneurship and Marketing Mix - Louise Panggabean, Helena; Subagio, Mochammad; Ayu Sofiati, Nunung; Candra Susanto, Primadi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Business management articles: Enterpreneurship and marketing mix analysis are scientific literature articles within the scope of marketing management science. The aim of this research is to build a hypothesis regarding the influence between variables which can later be used for futher research within the scope of marketing management. The research method used is descriptive qualitative. The data collection tecnique is using literature study. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and the journal Sinta. The results of this article are: 1) Enterpreneurship influences business management; and 2) Marketing Mix influences business management